(untitled) (The Planet, 2023)
Introduction: Acute respiratory infection (ARI) is one of the commonest causes of death in children in developing countries. They are responsible for 4 million deaths each year, and two-thirds of these deaths are in infants (especially young infants). The study aimed to analyze the pattern of upper respiratory infections among the school-going children treated at the combined military hospitalDhaka. Methods& Materials: This descriptive type of cross-sectional study was conducted at the OPD of CMH Dhaka and CWC Dhaka, Bangladesh for a period of 25 March 2012 to 30 June 2012. A total of 120 subjects were selected as per inclusion criteria.Result: In this study, the Greatest number of respondents (46.7%) had tonsillitis, (28.3%) pharyngitis, and the next significant number (15.0%) had epiglottitis, and the rest 6.7% and 3.3% had laryngitis and nasopharyngitisrespectively. Conclusion: The diseases which were found to be prevalent among the children were tonsillitis, pharyngitis, epiglottitis, nasopharyngitis, and laryngitis. In this study, the factors which were found to be high among the respondents were poor immunization, poor socioeconomic conditions, indoor air pollution, indoor smoking, and kaccha housing.